Petrography of the Nagar Parkar Igneous Complex, Tharparkar, Southeast Sindh - Jan, M. Qasim; Laghari, Amanullah; Khan, Mohammad Asif (Journal of Himalayan Earth Sciences, 1997)
The Nagar Parkar igneous complex in southern Tharparkar desert is a Late Proterozoic fragment of the western Indian shield. Six major magmatic episodes of intrusive and extrusive activity have been identified: 1) amphibolites and related dykes, 2) riebeckite-aegirine grey granite, 3) biotite-hornblende pink granite, 4) acid dykes, 5) rhyolite "Plugs", and 6) basic dykes. In terms of volume, the first three make most of the complex. The amphibolites, apparently forming basement for the subsequent intrusions, show low-grade metamorphism. The riebeckite-aegirine grey granite is mostly undeformed, and essentially composed of perthitic feldspar (microperthite, mesoperthüe) and quartz, with a small amount of plagioclase (albite-oligoclase), and characteristic presence of riebeckite and aegirine. The biotite-hornblende pink granite is mostly coarse- to medium-grained, and commonly homogeneous. It is generally leucocratic and essentially made up of perthitic feldspar, local microcline, quartz, and minor plagioclase (oligoclase), with biotite and hornblende as the varietal minerals along with iron-oxide. Some rocks contain sufficient plagioclase to be termed quartz monzonite or adamellite. The pink colour of the granite is due to hematitic staining resulting from alteration of ferromagnesian minerals. A wide range of minor accessory minerals occurs in the two types of the granite. The acid dykes, ranging from aplite to microgranite and rhyolite to quartz trachyte, contain phenocrysts of perthite, plagioclase and quartz in an allotriomorphic matrix of these minerals and accessory iron oxide, blue-green amphibole, biotite, zircon, apatite, fluorite, sphene, allanite and secondary epidote. Feldspar alteration (clouding, sericitization) imparts many of these a brownish colour. These rocks generally occur in small bodies but, locally (as in Dhedhvero), form up to 6 m thick dykes extending for more than 2 km. The rhyolites occur in two small, domal outcrops surrounded by alluvium, and may be an effusive phase genetically related to the granites. They are dark grey to black, glassy-looking rocks with whitish bands and consist of phenocrysts of feldspar and quartz in a very fine-grained matrix. All the major rock units of the complex are intruded by undeformed basic dykes, mostly less than 3 m thick, these show considerable petrographic variation and range from hornblende microdiorite to gabbro and dolerite, some of which contain titanian augite suggestive of alkaline affinity.